Design and development of Pahang black sambal cooking machine for Small and medium enterprises - Arman Shah bin Abdullah (Tanjong Malim, 2019)
Design and development of Pahang black sambal cooking machine for Small and medium enterprises by Arman Shah bin Abdullah